Importance of the cardiovascular physical examination in the diagnosis of coarctation of the aorta - Ana Rachel Carvajal Palacios (Medisur, 2021)
In the study of cardiovascular diseases, the importance of the medical history and physical examination cannot be underestimated. The primary care physician plays an important role in the assessment of neonates and the use of the clinical method is very important in this regard. The objective of this work is to call attention to the importance of the clinical method in the diagnosis of congenital heart disease.